Modelo simplificado para turbulência na camada limite noturna - Maroneze, Rafael (2016)
The appropriate estimation of turbulent fluxes in very stable conditions is a great challenge for numerical models that simulate the average behavior of the stable boundary layer. Although many features of the flow are usually reproduced, the intermittent variation turbulence is not simulated by most atmospheric models that use K theory for the determination of turbulent fluxes in the stable boundary layer. Moreover, the transition between the very stable and weakly stable regimes of the stable boundary layer is not well understood and described by numerical models. Therefore, in this work a one-and-a-half order numerical model is proposed to represent the average behavior of the nocturnal boundary layer. The model is based in the one proposed by Costa et al. (2011). In the presently proposed scheme, both the sensible heat flux and temperature variance are solved by prognostic equations in order to add degrees of freedom and physical detail to the model. Throughout the work, comparisons are made among the solutions varying different parameters. Results are also compared to the solutions obtained using the model proposed by Costa et al. (2011). The results show that the present model is able to reproduce the transition between the coupled and decoupled stable boundary layer regimes, in a manner similar to what is observed in nature. It also reproduces the occurrence of intermittent non periodical events and the formation of shallow mixing in weak wind conditions. The inclusion of prognostic equations for the sensible heat flux and for the temperature variance provides transitions between regimes at larger winds than those obtained when these quantities are parameterized, and closer to the observed values. The model provides a dependence of the potential temperature scale, θ∗ and of the sensible heat flux on the wind speed that is similar to observations. It also reproduces abrupt transitions between the stable boundary layer regimes, something not observed in the model proposed by Costa et al. (2011). The turbulent kinetic energy balance obtained by the model is closer to the observed by Acevedo et al. (2016) than was obtained by Costa et al. (2011). Dissipation is the dominat mechanism of turbulence destruction in very stable conditions, a role played by buoyant destruction in the model by Costa et al. (2011). The results sustain the hypothesis proposed by Van Weil et al. (2012), that the very stable regime happens when turbulence is not capable of sustaining turbulent heat fluxes large enough to accompany the long wave radiative loss.